2013
DOI: 10.1136/annrheumdis-2012-202976
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Ankylosing Spondylitis Disease Activity Score (ASDAS) in patients with early spondyloarthritis from the Esperanza programme

Abstract: ASDAS performed as a valid activity score even being slightly better than the Bath Ankylosing Spondylitis Disease Activity Index in its ability to discriminate between high and low disease activity in early SpA. ASDAS performed similarly in AS, early forms of SpA, non-radiographic axial SpA and peripheral SpA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 10 publications
2
27
0
Order By: Relevance
“…ASDAS has been validated in several cohorts and different subgroups of patients with AS. Espartero et al conducted a study in 672 early SpA patients and reported that ASDAS had a high validity in the assessment of disease and performed similarly as in patients with AS [29]. There is only one study investigated the validity of ASDAS in the assessment disease activity in patients with axPsA [14].…”
Section: Discussionmentioning
confidence: 99%
“…ASDAS has been validated in several cohorts and different subgroups of patients with AS. Espartero et al conducted a study in 672 early SpA patients and reported that ASDAS had a high validity in the assessment of disease and performed similarly as in patients with AS [29]. There is only one study investigated the validity of ASDAS in the assessment disease activity in patients with axPsA [14].…”
Section: Discussionmentioning
confidence: 99%
“…Originally, it was calculated by two formulas according to the acute phase reactants used (either C-reactive protein [CRP] or erythrocyte sedimentation rate [ESR]), and the ASDAS-CRP was reported as the preferred formula [6]. The discriminative ability and the sensitivity to change of the ASDAS have been tested in multiple databases and clinical trials, and it was also further validated in various populations [1,[7][8][9][10][11][12][13][14][15]. However, the calculation of the ASDAS can be relatively complex and requires a calculator.…”
Section: Introductionmentioning
confidence: 99%
“…Given its face validity and its psychometric properties,13 14 we proposed to use ASDAS to define the trajectories of disease activity over time in an axSpA cohort.…”
mentioning
confidence: 99%